The Effectiveness of ICT Integration in Teaching Science Concepts (American Journal of Multidisciplinary Research and Innovation, 2022)
This study determined the effectiveness of ICT in teaching science concepts. This study utilized a true experimental design, specifically the pretest-posttest two-group design. A teacher- made test was used as pretest and posttest to assess the pupils’ level of knowledge about science concepts. The subject of the study was a rural school in Ilocos Norte. One class was assigned as the control group while the other was the experimental group. Data were analyzed using frequency counts, percentage distributions, means, standard deviations, t-test of correlated of dependent samples and t-test of difference. The results showed a significant difference between the pretest and posttest mean scores of the two groups with their posttest mean scores being significantly higher than their pretest mean scores, indicating that the two methods were effective in teaching Science concepts.  However, the results of the t-test of difference between the posttest mean scores of the two groups showed that the posttest mean score of the experimental group was significantly higher than that of the control group.  This implied that the ICT integration were more effective than the lecture-discussion method in teaching science concepts to the grade five pupils.